Evaluation of zeolite supported bimetallic nanoparticles of zero-valent iron and copper (Z-nZVI/Cu) in the presence of ultrasonic for simultaneous removal of nitrate and total coliforms from aqueous solutions: optimization and modeling with response surface methodology. (2nd October 2021) - Seid-Mohammadi, Abdolmotaleb; Asgari, Ghorban; Rahmani, Alireza; Madrakian, Tayyebeh; Karami, Amir
Abstract: In this study, the removal of nitrate and total coliforms by zeolite-supported bimetallic nanoparticles of zero-valent iron and copper (Z-nZVI/Cu) coupled with ultrasonic treatment was studied. The Z-nZVI/Cu catalyst was synthesized by ion exchange method and was characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The results of analyzes were indicative of the appropriate synthesis of catalyst and high distribution of iron and copper nanoparticles on zeolite. The effects of different operating parameters such as initial pH, catalyst concentration, initial concentration of pollutants, and catalyst concentration on removal of nitrate and total coliforms were investigated. The results showed that nitrate removal efficiency decreased with increasing pH and initial concentration of nitrate, while it increased by increasing the concentration of catalyst and ultrasonic frequency. To eliminate total coliform, the same trend was observed, except for increasing the removal efficiency by increasing the total coliform concentration. The results of optimization by response surface methodology (RSM) show that the maximum removal efficiency of nitrate and coliform were 97.77 and 97.77%, respectively. The results of the comparative experiments between the various processes showed that the ultrasonic process alone and ultrasonic coupled with Z-nZVI/Cu catalyst are suitable to provide the highest removal of total Coliforms and nitrate from aqueous solutions, respectively.